Development of novel Co-MOF loaded sodium alginate based packaging films with antimicrobial and ammonia-sensitive functions for shrimp freshness monitoring. (February 2023) - Feng, Shaoxiong; Tang, Qun; Xu, Zongshu; Huang, Kangqi; Li, Heping; Zou, Zhiming
Abstract: It is highly desirable to develop intelligent active packaging films with ammonia-sensitive performance to maintain and monitor the freshness of meat food as the ever-increasing requirement for food safe. Herein, novel cobalt-based metal-organic framework (Co-MOF) nanoparticles with ammonia-sensitive and antibacterial functions were successfully synthesized and then introduced into sodium alginate (SA) matrix to fabricate SA-based intelligent active packaging films by solution casting method. The effects of Co-MOF introduction on the structure, physical and functional features of the SA film were systemically studied. The results revealed that the Co-MOF nanofillers were uniformly distributed in the SA matrix, leading to obvious enhancements on tensile strength, toughness, thermal stability, UV-shielding and water vapor barrier capability of SA film. Moreover, the resultant SA/Co-MOF composite films showed outstanding antibacterial activity and ammonia-sensitive discoloration performance. When applied to monitor shrimp spoilage, the color of SA/Co-MOF composite films turned from pale pink to brownish black. These results suggested that the developed SA/Co-MOF films could be utilized as active and intelligent food packaging materials. Graphical abstract: Image 1 Highlights: Novel Co-MOF loaded sodium alginate based intelligent active films were developed. The films exhibited good tensile strength, toughness, and water barrier properties. The films exhibited outstanding antibacterial and ammonia-sensitive functions. These intelligent films were successfully applied for shrimp freshness monitoring.